Can a Single General Self-Rated Health Question Mirror Social Determinant of Health? - Zahed Rezaei; Nastaran Keshavarz Mohammadi; Hamidreza Pouragha; Elham Shakibazadeh (Tehran University of Medical Sciences, 2022)
Background: Self-rated health (SRH) indicator is widely used and recommended in health research as a standard indicator for measuring health in different populations. This paper reports SRH of employees at Tehran University of Medical Sciences (TUMS), Tehran, Iran; and its related factors. Methods: We used the TUMS Employee's Cohort Study (TEC) data, collected from September 2017 to August 2019. SRH of 2158 employees were assessed using a single question. Univariate and multivariate logistic regression were performed to determine factors associated with sub-optimal SRH. Results: Overall, 14.9% (n = 321) of respondents rated their health as sub-optimal. Differences were observed with subgroups. Women, lower socioeconomic status (SES), experiences of more economic fluctuation conditions and lower reading scores could predict sub-optimal SRH variations in crude and adjusted regression analyses. The age, social capital, work experience and employment status could predict sub-optimal SRH variations only in crude regression analyses (P<0.05). Conclusion: Differences in SRH report reflected differences in socioeconomic conditions. The biggest gap was observed between people of different SES (five times). Considering that SRH reflected socioeconomic characteristics of individuals, it may be considered as a quick, non-expensive, and simple way of identifying groups in need of addressing their social determinants of health.